Improving Balaghah Mastery Through Teams Games Tournaments with Crossword Puzzle Media in Higher Education - Hasibuan, Renni; Hasanah, Mamluatul; Faisol (Al-Lisan: Jurnal Bahasa, 2024)
The selection of appropriate teaching methods by educators and the optimization of learning media utilization are crucial factors in achieving success and effectiveness in the learning process. Accordingly, this research aims to examine the impact of using the Teams Games Tournament method with crossword puzzle media on the learning outcomes of Balaghah (Arabic rhetoric) students at the State Islamic University Imam Bonjol Padang. This research employed a quantitative approach with a quasi-experimental pretest-posttest control group design. Data collection techniques involved administering pretests and posttests to both the control and experimental groups. The collected data were analyzed using descriptive statistical tests, tests for normality and homogeneity (Kolmogorov-Smirnov test), and independent sample t-tests. The research results indicated a significant variation in student learning outcomes before and after using the Teams Games Tournament method with crossword puzzle media in Balaghah learning. Based on the findings, the average pretest scores for the experimental group and control group were 52.83 and 52.23, respectively, while the average posttest scores for the experimental group were 92.87 and 81.46 for the control group. The independent sample t-test showed a significance value of 0.000 < 0.05, indicating sufficient evidence to support the alternative hypothesis (Ha). Therefore, it was concluded that there was a significant difference in student learning outcomes before and after implementing the Teams Games Tournament method with crossword puzzle media in Balaghah learning. These findings validated the effectiveness of this method in enhancing understanding and student learning outcomes in Balaghah material.